2013
DOI: 10.1088/0953-8984/25/44/445004
|View full text |Cite
|
Sign up to set email alerts
|

Iridium-modified Si(111) surface

Abstract: The physical and electronic properties of Ir-modified Si(111) surface have been investigated with the help of STM (scanning tunneling microscopy) and LEED (low energy electron diffraction). The LEED pattern of the surface exhibits [Formula: see text] reconstruction. STM images show that [Formula: see text]° reconstruction originates from the Ir-ring clusters. STS (scanning tunneling spectroscopy) measurements on the ring clusters reveal a state located about 0.3 eV below the Fermi level. A careful analysis sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 15 publications
(15 reference statements)
3
7
0
Order By: Relevance
“…Recently, three studies focusing on Ir modified semiconductor surfaces have been reported. [6][7][8] Two of these studies focuses on the formation of Ir nanowires on Si(0 0 1) and Ge(0 0 1) surfaces [5,6]. Similar nanowires were previously reported on Pt and Au modified Si( 0 0 1) and Ge(0 0 1) surfaces.…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…Recently, three studies focusing on Ir modified semiconductor surfaces have been reported. [6][7][8] Two of these studies focuses on the formation of Ir nanowires on Si(0 0 1) and Ge(0 0 1) surfaces [5,6]. Similar nanowires were previously reported on Pt and Au modified Si( 0 0 1) and Ge(0 0 1) surfaces.…”
Section: Introductionsupporting
confidence: 57%
“…Such systems offer unique opportunities to study quantum nature of one-dimensional systems. In [8] a LEED and STM/STS study on Ir modified Si(1 1 1 ) surface was reported. The LEED profile of the surface exhibits × − °7 7 R19.1 reconstruction.…”
Section: Introductionmentioning
confidence: 99%
“…The islands are similar in size and shape; however, island in Figure b have SLD’s, whereas the island in Figure a is flat and featureless. The wetting layer surrounding the island is made out of Ir-ring clusters that form domains on Si(111). , Ring clusters consist of a transition metal surrounded by six Si atoms, three of which directly bind to the transition metal and are called bridging adatoms and the remaining three Si atoms, called the capping adatoms bind two bridging adatoms and one Si substrate atom. The Ir/Si(111) system exhibits Stranski–Krastanov-type growth.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Since these substrates are mainly used in semiconductor industry, they can provide a smooth transition from a prototype in a research lab to a consumer product. Some of these structures have high aspect ratios; therefore, they are called nanowires.…”
Section: Introductionmentioning
confidence: 99%